(-)-Amarbellisine is none other than (-)-montanine: A CASE-3D and dereplication NMR study. (April 2023) - Navarro-Vázquez, Armando
Abstract: The 2013 total synthesis of the putative structure of the (-)-amarbellisine lycorine alkaloid reported very significant differences between the 1 H and 13 C NMR spectra of the synthesized product and the originally isolated alkaloid, and it was hypothesized that the correct structure should be a diastereoisomer of the originally proposed one. The present CASE-3D configurational analysis, based on DFT predictions of 13 C chemical shifts, provided very bad fits for all possible diastereoisomeric lycorine-type structures and reexamination of the NMR data reported for natural (-)-amarbellisine revealed several inconsistencies with the proposed lycorine-like structure. Dereplication of the original 13 C shifts and literature searching showed that (-)-amarbellisine is none other than the well-known (-)-montanine alkaloid. Graphical Abstract: ga1 Highlights: Structural revision. Lycorine alkaloids. Montanine alkaloids. DFT prediction of chemical shifts. Dereplication.